Eartbworms as biosindicators of metal poHution in dump sites of Abeokuta City, Nigeria - Bamgbose, O (2000)
Metal concentrations (Zn, Pb, Mn, Cu, Cd and Cr) and contents were measured in earthworms (Libyodrilus violaceus) and soil samples from three non-contaminated sites an.d ten dump sítes located in Abeokuta, Nigeria. Samples from control sites show (in general) levels of metals to be higher in earthworms than in soil samples, as shown by the mean concentrations, (earthworms-soil: - Zn:7.02, 6.74, Pb:5.04, 4.94, Mn 10.54, 10.41, Cu:l.03, 1.60, Cd: 0.80, 0.81 and Cr:0.55, 0.49 Ilglg) while for samples from dump sites, irrespective of Ihe degree of pollution, the ratio of metal concentration in earthworms to soil samples were less than unity with the exception of Cd and Cr. The availability of metals in soils was also co-determined by the soil pH and soil organic malter which accounted for the trend of metal concentration al the various dump sites. For Ihe control sites, the pH ranged from 5.40 - 6.74 and soil organic malter from 3.25 % lo 3.40 %, while for the dump sites, values of 7.44-lO.lO and 5.79 % - 7.59 % were obtained for soil pH and soil organic malter respectively. The metal ion concentration in both soil and earthworm samples followed the trend Pb > Zn > Mn > Cu > Cr > Cd. Dump sites with high levels of Pb were located by roadsides of busy highways.